A Nonfunctioning Pituitary Macroadenoma Presenting as Cyclical Vomiting and Severe Hyponatremia in a Young Female - Dinuka S. Warapitiya; Dimuthu Muthukuda; W. A. H. P. Sanjeewa; Kushalee Poornima Jayawickreme; Shyama Subasinghe (Case Reports in Endocrinology)
Introduction. Recurrent vomiting is a commonly overlooked debilitating symptom which causes significant impact on the quality of life. There are several causes for vomiting, ranging from commonly known causes to rare causes. Nonfunctioning pituitary macroadenomas generally present with visual disturbances, headache, and symptoms due to anterior pituitary hormone deficiencies. This case report is about an atypical presentation of a nonfunctioning pituitary macroadenoma in which the patient presented with cyclical vomiting with severe hyponatremia. Case Report. A 23-year-old girl presented with four to five episodes of vomiting per day for two days duration. She had a history of similar episodes of vomiting since 2016, with each episode generally lasting for 4-5 days and occurring in every four to six months. All episodes exhibited similar symptomatology and she was free of symptoms in-between. Generalized body weakness, postural dizziness, reduced appetite, and secondary amenorrhea were other symptoms she has had since 2016. Examination findings showed a low body mass index (BMI) (16 kg/m2) with normal system examination. Investigations showed severe hyponatremia (110 mmol/L) with hypokalemia (3.2 mmol/L) and hypochloremia (74 mmol/L). Her urinary excretion of potassium, sodium, and serum osmolality was low. Urine osmolality was mildly elevated compared to serum osmolality. Blood urea was normal. Severe hyponatremia with minimal hyponatremic symptoms was suggestive of chronic hyponatremia, which was accentuated by ongoing vomiting and possible reduced intake of salt. Further investigations showed evidence of secondary hypoadrenalism, central hypothyroidism, hypogonadotropic hypogonadism, and mild hyperprolactinemia. Magnetic resonance imaging (MRI) revealed a pituitary macroadenoma with mass effect on the optic chiasma. Hydrocortisone and levothyroxine were started, and she underwent transsphenoidal resection of the pituitary tumor. She recovered from cyclical vomiting. Conclusion. There can be multiple overlapping aetiologies for every observed symptom, sign, and abnormal investigation finding. Therefore, aetiological diagnosis is challenging, especially in the presence of an atypical clinical presentation. Cyclical vomiting and severe hyponatremia are atypical presentations of nonfunctioning pituitary macroadenomas.